Transformative leadership adoption assessment a manual for cooperatives. (Asian Women Co-operative Development Forum, 2005)
Contents: Glossary. Acronyms about Cooperatives and Transformative leadership to co-operatives. Standards for stages of development and general level of adoptions of transformative leadership. Procedures for the assessment of co-ops' general level of adoption of transformative